Application of Means Ends Analysis (MEA) Learning Model in Attempt to Improve Student’s High Order Thinking - Riana, Alif Aulya (Universitas Pendidikan Indonesia, 2017)
This study is based on the problems that occur in IPS learning in class VIII-D students of SMPN 5 Bandung that is teacher-centered in the classroom and the ability of students to think high-order are still low. The alternative problem solving chosen is by applying the Means Ends Analysis (MEA) learning model. Based on the background, the formulation of this study problem is how the planning, implementation, implementation results and what are the obstacles of the learning model Means Ends Analysis in attempt to improve the ability of high-order thinking. Reviewing the problems to be studied in relation to the learning process, the author chose Classroom Action Research (PTK) with Kemmis and Taggart cycle model in 3 cycles with 12 actions. Implementation of learning by using learning model Means Ends Analysis in improving the ability of students high-order thinking are said to succeed. The improvement of high-order thinking ability of students can be seen from the development of aspects that becomeindicators of high-order thinking. All aspects of this indicator have evolved from cycle 1 to cycle 3, from which initially the quality is less, it is sufficient to improve. In conclusion, the implementation of learning model Means Ends Analysis can improve the ability of high-order thinking of students in IPS learning. This is supported by the achievement of all indicators in analyzing and evaluating. Both are in good categories and indicators to create are in enough category.